2014
DOI: 10.1007/s00128-014-1388-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation and Interaction of Quinoline and Glucose in Dual Substrates System

Abstract: An indigenous mixed culture of microorganisms, isolated from a full-scale coal gasification wastewater treatment plant, was used in degrading quinoline in presence of glucose as an alternative carbon source. The results showed that biodegradation kinetics of both quinoline and glucose could be described by first-order reaction kinetics model. It was also found that the biodegradation rate of quinoline was accelerated by the presence of glucose, while glucose degradation was inhibited by the presence of quinoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…While the concentration of 500 mg quinoline /L could be degraded within 14h. This could be attributed to the effect the degradation time by the increasing the inhibitory effect of the quinoline as its concentration was increased and indicated that the quinoline degradation rate was increased with the initial quinoline concentrations (within 500 mg/L), the results were similar to the conclusion of (Wang et al, 2001;Xu et al, 2015).…”
Section: Effect Of Quinoline Concentrationsupporting
confidence: 81%
“…While the concentration of 500 mg quinoline /L could be degraded within 14h. This could be attributed to the effect the degradation time by the increasing the inhibitory effect of the quinoline as its concentration was increased and indicated that the quinoline degradation rate was increased with the initial quinoline concentrations (within 500 mg/L), the results were similar to the conclusion of (Wang et al, 2001;Xu et al, 2015).…”
Section: Effect Of Quinoline Concentrationsupporting
confidence: 81%
“…It was demonstrated that glucose could induce the formation of monooxygenase required for the transformation of many recalcitrant compounds such as quinoline. In addition, the consumed NADH necessarily used for the biological process could be efficiently regenerated through glucose oxidation 31 , Although the mechanisms for the cometabolic degradation of various pollutants by microbes were rather complicated, the first step was considered to be the utilization of easily degradable substrate by microbes and the production of catabolic enzymes with broad substrate specificity, which could be used for the degradation of recalcitrant substrate 32 . What’s more important, the addition of organic carbon source often results in the increase of biomass, which is beneficial for the degradation of various recalcitrant substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Although physicochemical methods have been extensively reported with promising results, limited application for nitrogen and carbon removal, high treatment cost, system complexity, and lack of proper management of toxic end-products are the main shortfalls that strongly limit their long-term application . Hence, biological methods are still preferable options because of the lower energy requirements and special capabilities in the treatment and disposal of a variety of pollutants. …”
Section: Introductionmentioning
confidence: 99%